The Impact of Commercial Caravans Crossing the Sahara on the Archaeological Heritage of Southern Algeria - Sagueni, Mahammed (Historical Studies, 2025)
Keywords: Commerce transsaharien

Sedrata-Sijilmassa: sur la piste d'un art islamique transsaharien - Capel, Chloé (2025)
Keywords: Commerce transsaharien

Acteurs et itinéraires du commerce des esclaves au temps des empires soudanais Soninké et Manding - Coulibaly, Pédiomatéhi Ali (Rivages, 2025)
This study analyzes the actors, networks, and commercial routes that structured the trans-Saharan slave trade during the Soninke and Manding empires (8th–13th centuries) through a critical examination of Arabic-Islamic sources, including alYaʿqūbī, al-Idrīsī, Ibn al-Fakīh, and Ibn Ḥawqal, supplemented by modern historiography. While the trade predated Islam, it intensified significantly following Arab-Berber expansion into the Sahel, operating through collaboration between Sudanese rulers who organized slave raids and market provisioning, and Maghrebi and Eastern merchants (particularly Ibadite Berbers) who established purchasing posts, financed caravans, and secured desert passage. Three principal itineraries channeled enslaved populations northward: the western Tahert–Sijilmassa–Awdaghost–Ghana axis; the Tripoli–Zawila–Kanem corridor linking Fezzan to Lake Chad; and an Egypt–Ghana route traversing Gao, Kawar, and the Kharga/Dakhla oases. Religious-legal discourse, notably the equation of unbelief (kufr) with enslavability, as articulated in Aḥmad Bābā's legal opinions, and elite demand for luxury commodities sustained capture and exchange, with urban centers like Koumbi Saleh, Awdaghost, Gao, and Zawila serving as nodal points. By correlating political chronologies with documented caravan geography, the research illuminates how state authority, commercial mediation, and desert infrastructure converged to transform localized enslavement into systematic trans-Saharan labor traffic supplying North Africa and the Middle East.
Keywords: Commerce transsaharien

Sijilmasa: The Capital of Gold and Trade Caravans During the Reign of the Banu Midrar (140 AH – 366 AH / 757 CE – 976 CE) - Ahmed, Naima Abdulmawla Salem (Bani Waleed University Journal of Humanities and Applied Sciences, 2025)
During the reign of the Banu Midrar (140–366 AH / 757–976 CE), the city of Sijilmasa witnessed significant economic development in various aspects, particularly in trade. This study focuses on the role played by the Banu Midrar in revitalizing commercial caravan routes and organizing trade networks during their rule. It also highlights their efforts to establish extensive trade relations with the Eastern Islamic world, North Africa, al-Andalus, and Sub-Saharan Africa, with gold being one of the most prominent commodities exchanged. The researcher adopted an analytical inductive approach to examine historical events and facts and to understand the motivations behind the imposition of taxes and customs on land and maritime trade by the Banu Midrar, which contributed to elevating Sijilmasa’s global commercial status during the 2nd to 4th centuries AH (8th to 10th centuries CE). Additionally, the researcher employed the descriptive method to trace and analyze historical developments, while also incorporating other scientific methodologies where necessary. This approach led to findings that underscore the pivotal role of the Banu Midrar Emirate in the flourishing of trade in Sijilmasa.
Keywords: Commerce transsaharien; Histoire – Sidjilmassa

العلاقات التجارية والثقافية بين المغرب والسودان الغربي خلال القرنيين الثاني والثالث الهجريين - حبيبي, إسماعيل (دورية کان التاريخية: المستقبل الرقمي للدراسات التاريخية, 2025)
Keywords: Commerce transsaharien

التجّار العرب نشروا الإسلام في أدغال أفريقي (العرب, 2023)
Keywords: Commerce transsaharien

السياسة الخارجية لمملكة مالي الإسلامية (597-886 هـ /1200-1484 م) - عسيري, حسن حلمي أبو الفضل (مركز جمعة الماجد للثقافة و التراث, 2012)
Keywords: Commerce transsaharien; Mali – Histoire

Traites sahariennes et réseaux ibadites médiévaux (VIIIe -XIIIe siècle) - Aillet, Cyrille (Rivages de traite et frontières d'esclavage: Mondes ibériques, maghrébins et ouest-africains (VIIIe-XIXe siècle), 2024)
Keywords: Commerce transsaharien

علاقات إياضية بلاد الجريد مع بلاد السودان خلال العصر الوسيط او رحلات إباضية الجريد إلى بلاد السودان مراوحة بين التجارة والتبشير - النوري, نور الدين (2024)
Keywords: Commerce transsaharien

New historiographical perspectives on the medieval Saharan space: human dynamics and intra-African and intra-Islamic religious and intellectual exchanges up to the 16th century - Novo, Marta G.; Gómez, María Crego; Patarnello, Claudia (2022)
Keywords: Commerce transsaharien

التجارة الإباضية ودورها في نشر الاسلام بالسودان الغربي من خلال المصادر الإباضية - الزرويل, صالح (عصور, 2024)
انتشر الإسلام في ربوع بلاد السودان الغربي في وقت مبكر، ويعود الفضل في ذلك لمختلف التجار الدعاة الذين استطاعوا بمعاملاتهم التجارية وأخلاقهم الإسلامية السامية أن يؤثروا في عامة شعوب جنوب الصحراء وخاصتهم، وكان التجار الإباضيون من بين أولئك الذين أسلمت على أيديهم جحافل كبيرة من ساكنة المنطقة. فالتجارة الإباضية موغلة في القدم مع تلك الربوع، وقد تحدثت عنها كتب التاريخ فضلا عن كتب الرحلات والجغرافية، وانفردت بذكر أسمائهم المصادر التاريخية الإباضية التي تم تأليفها خلال الفترة الوسيطة مثل: سير الورجلاني وطبقات الدرجيني وسير الشماخي. بتتبّعنا وفق مسار كرونولوجي لقائمة أولئك التجار؛ وجدنا بأن التجارة والتجار الاباضيون كانوا في وتيرة متباينة عبر القرون، وأن التجارة الإباضية كانت ذات أبعاد دينية واجتماعية وسياسية فضلا عن البعد الاقتصادي الرئيس، وأن الأشخاص الذين تداولت أسماؤهم مختلف كتب السير والطبقات لم يكونوا ذوو مستوى عال من العلم، أو مناصب عليا في بلدانهم، لكن أمانتهم ونزاهتهم في معاملاتهم التجارية جعلت سكان مناطق بلاد السودان وممالكها تعتنق الإسلام أفواجا. Islam spread throughout Western Sudan at an early date, who, through their commercial dealings and their lofty Islamic morals, were able to influence the generality of the peoples of sub-Saharan Africa and their own. The Ibadi merchants were among those through whom large hordes of the region’s inhabitants converted to Islam. Ibadi trade with those regions is very ancient, and the Ibadi historical sources that were written during the intermediate period are the only ones mentioned by their names, such as: The Biography of Tabaqat Al-Darjini,. By following a chronological path to the list of these merchants; We found that Ibadi merchants were at a different pace over the centuries, and that had religious, social, and political dimensions in addition to the main economic dimension, However, their honesty and integrity in their commercial dealings made the inhabitants of Sudan’s regions and kingdoms embrace Islam in droves.
Keywords: Commerce transsaharien

The Ibadi Trading Communities of the Maghreb (Eighth to Eleventh Century) - Aillet, Cyrille (Land and Trade in Early Islam: The Economy of the Islamic Middle East 750-1050 CE, 2025)
Land and Trade in Early Islam discusses the latest developments in the field of early Islamic economic and social history, and explores the notion of polycentrism and the dialectic between global and local between 700 and 1050 CE. The volume explores the political mechanisms and the role of Islamic states in regulating and developing demand in the economy. The chapters question the binary of core/periphery, and demonstrate how the growing scholarship on the liminal regions of the Caliphate has transformed our understanding of the early Islamic world by offering a more nuanced picture of its regional urban and socio-economic dynamics. Changes in the peripheries of the early medieval Caliphate have traditionally been conceived as resulting from initiatives by the core. An increased focus on the comparatively under-explored regions in central Asia, north Africa, south-east Asia and the Caucasus has thrown this into question. Land and Trade in Early Islam draws on this growing body of scholarship to question the notion of peripherality, explore lines of economic influence and interdependence, and to better understand the regional economic, social and political dynamics of this period.
Keywords: Commerce transsaharien

الإباضية ودورهم في نشر الإسلام في بلاد السودان الغربي - ناصر, محمد صالح (مجلة جامعة سنار, 2018)
Keywords: Commerce transsaharien

Le commerce transsaharien à la lumière de l’ibadisme maghrébin : cultures économiques, marchés et réseaux médiévaux - Aillet, Cyrille (2017)
L’historiographie a maintes fois souligné le rôle pionnier des populations berbères affiliées à la doctrine dissidente de l’ibadisme dans le développement du commerce transsaharien, en particulier la traite des esclaves. Cette branche de l’islam serait en effet une parfaite illustration de « l’ascétisme intramondain » mis en avant par Max Weber dans son analyse des relations entre religion et économie. Nous reviendrons ici sur la place de cette minorité dans l’évolution des économies sahélo-méditerranéennes, sur ses modes d’interaction sociale, sur ses pratiques et représentations économiques
Keywords: Commerce transsaharien

دور إباضية المغرب الأوسط في تنشيط التجارة الصحراوية خلال العصر الوسيط - بوسالم, أحلام; عابد, يوسف (الحوار المتوسطي, 2020)
تحاول هذه الدراسة تسليط الضوء على أحد أهم المكونات الاجتماعية لبلاد المغرب الأوسط خلال العصر الوسيط، وهي -الجماعة الإباضية- والتي لعبت دورا كبيرا في الحياة السياسية والعلمية والمذهبية، غير أن أكبر أدوارها تجلت في الحياة الاقتصادية، حيث تحول مجالها والحواضر التابعة لها إلى أسواق ومراكز استقطاب اقتصادي كبير، وأصبح تجارها يلعبون دور الوساطة في التجارة العالمية عموما والمغربية على وجه الخصوص، وهذا باحترافيتهم وتحكمهم في تجارة بلاد السودان، وهذا الدور لهذه الجماعة هو موضوع دراستنا. Abstract: This study focuses on one of the most important social components of the countries of the Maghreb during the medieval period, which is the Ibadi community, which played a major role in political, scientific and sectarian life, but the biggest roles manifested in in economic life, as its field and its metropolitan areas turned into markets and centers of major economic polarization, and its merchants have become playing the mediating role in global trade in general and middle Maghreb in particular, and this is with their professionalism and control over the trade of western Sudan, and this role for this group is the subject of our study
Keywords: Commerce transsaharien

دور تيهرت في التواصل الإقتصادي بين بلاد المغرب الإسلامي والسودان الغربي ق 2-5هـ-8-11م - حراق, إسحاق (جامعة قسنطينة 2, 2015)
Keywords: Commerce transsaharien

L'Afrique aux XVIe et XVIIe siècles, loin des préjugés (Libération, 2017)
Le nord-est du Nigeria a été le berceau du royaume du Kanem-Borno qui dominait le bassin du lac Tchad aux XVIe et XVIIe siècles. «La région du lac Tchad ...
Keywords: Commerce transsaharien

L'archipel ibadite : Une histoire des marges du Maghreb médiéval - Aillet, Cyrille (Ciham éditions, 2022)
Cette enquête inédite revisite l’évolution du Maghreb médiéval à partir de ses marges. Elle dévoile l’histoire de l’ibadisme, une minorité aujourd’hui invisible dans l’océan du sunnisme, mais qui a puissamment façonné le Maghreb. Héritiers des dissidents kharijites soulevés contre le califat, les Ibadites animent les révoltes qui détachent la région de l’Empire. Ils jouent un rôle crucial dans l’émergence d’un discours en faveur des Berbères, chez qui ils recrutent en masse. Ces contestataires développent une doctrine politique singulière, hostile à la tyrannie et favorable à une souveraineté fondée sur l’élection, la consultation et la collégialité. Pour les Ibadites, cet idéal s’incarne dans l’État qu’ils fondent vers 761 près de Tiaret, dans l’Algérie actuelle. Dirigé par une dynastie d’imams persans, il symbolise pour eux un véritable âge d’or. Sa disparition brutale sous les coups des Fatimides en 909 constitue un traumatisme collectif. Elle oblige les fidèles à se redéployer sous la forme d’un archipel de communautés autonomes, dispersées entre la Méditerranée et le nord du Sahara. Après l’échec des derniers soulèvements berbères face à l’Empire, la nécessité de coexister avec les pouvoirs dominants s’impose. L’autorité des notables et des oulémas se substitue localement à l’État pour assurer la cohésion collective. Le commerce transsaharien tisse des relations entre ces communautés et assure la fortune des marchands- lettrés qui traversent le désert jusqu’à Ghana, Gao ou au lac Tchad. Ils en rapportent de l’or et des convois d’esclaves, revendus dans les oasis et les cités de Méditerranée. La poussée des intérêts rivaux et l’expansion religieuse du malikisme et du soufisme achèvent toutefois d’éroder, puis de désarticuler, l’archipel ibadite. À la fin du Moyen Âge, il n’en subsiste que les bastions actuels du Mzab, de Tripolitaine et de Djerba. La mémoire de cette communauté oubliée nous plonge au cœur même de la genèse de l’Islam et du Maghreb.
Keywords: Commerce transsaharien; Dynastie rustumide; Ibadisme – Afrique du Nord

Les routes ibadites transsahariennes - Oussedik, Fatma (2018)
Durant des siècles, à travers le Sahara, des êtres et des biens ont été échangés, de même que les modèles culturels et les croyances religieuses. Ces échanges se sont accompagnés d’une propagation de l’Islam. Dans cet espace africain, des auteurs distinguent : – Les traites « internes » à l’Afrique noire, caractérisée par leur longévité (VIIe au XIXe siècle) et leur extension géographique. – Puis, les traites « orientales » qui concernent plus précisément le monde musulman. Elles suivent les routes sahariennes et celles qui relient l’Afrique de l’Est et la mer Rouge. Elles se sont accompagnées d’une islamisation des populations. -Enfin, la traite « occidentale » et ses différentes phases (Eric Mesnard et Aude Désiré, Enseigner l’histoire des traites négrières etde l’esclavage-cycle 3, 2007). Notre propos concerne donc la seconde période qui, selon Olivier Pétré-Grenouilleau, aurait concerné, du VIIe au XXe siècle, 17 millions d’individus. Les « traites internes» concernèrent 14 millions pendant la même période et la « traite atlantique » 11 millions de personnes du XVIe au XXe siècle (Olivier Pétré-Grenouilleau, les traites négrières. Essai d’histoire globale, 2004). Mais il faut aussi distinguer au moins deux périodes dans l’Islamisation, qui a marqué la phase qui nous intéresse, de populations vivant au sud du Sahara, en particulier en Afrique de l’Ouest. Ces deux étapes différentes sont celles du commerce transsaharien puis des conquêtes proprement guerrières. Les liens religieux entre les Ibadites du M’zab et l’Afrique sub saharienne se sont surtout noués durant la première partie mais ils ont aussi participé à la seconde. Notre intervention s’attardera sur la connaissance et la réactivation actuelle de ces routes par les passeurs qui organisent les mouvements de population entre l’Algérie et les pays au sud du Sahara. Comme nous essaierons de montrer que ces mouvements réactivent les récits d’origine des populations noires vivant au M’zab.
Keywords: Commerce transsaharien

Proselytisme kharejite et commerce transsaharien : cas de la cité de Sijilmassa à l'époque midrarite - Ramsi, Ahmed (Université Paris 8, 2000)
Keywords: Commerce transsaharien

Traders, Saints, and Irrigation: Reflections on Saharan Connectivity - Scheele, Judith (The Journal of African History, 2010)
Studies of trans-Saharan trade have recently been revitalized, mainly through an exploration of local archives. These archives offer a further possibility: to investigate the link between local settlement and wider patterns of exchange. Material from southern Algeria and northern Mali suggests that oases were not viable without outside investment, that pastoral economies needed storage space and agricultural produce, and that intra-Saharan and trans-Saharan trade relied on each other. Hence, regional mobility and outside connections were not subsidiary but constitutive of the local, and local patterns of production and trans-Saharan commerce were aspects of the same system.
Keywords: Commerce transsaharien

Stratégies ibadites de contrôle des axes commerciaux et de l’espace saharien - Belhachemi, Faouzia (Les sociétés civiles face au marché: le changement social dans le monde postcolonial, 2000)
Keywords: Commerce transsaharien

Djenne et le Ghana : deux modeles sociaux, et la question du commerce trans-saharien - Ogino, Isabelle Seeleman (The Annual of the Institute of Economic Research, 2014)
This paper puts under scrutiny the alleged link between the Trans-Saharian Arabo-Berber trade and the development of complex polities such as the Ghana empire in the West African Sahel. When did Ghana come into existence? As evidence is lacking, the city of Djenne (Jenne) could provide some clues. Meanwhile, the peculiar urbanism of Djenne-Djeno (old Jenne) can be understood as depicting alternative, auto-organizing social relations in the Inland Niger Delta. Furthermore, during the first millennium before and the first millennium after common era, the distinctive «urban cluster» pattern of Djenne-Djeno or Dia in the Macina can be found elsewhere along the Niger Bend and as far downstream as Bentia-Kukiya. Climatic changes affecting the Sahara presumably induced a common Soninke origin for Djenne-Djeno and for the Ghana polity, in both cases via the Neolithic culture of Tichitt. Based on this and on the Wagadu myth of the snake and the rain-maker, some features of Ghana can be underlined. Specifically, the level of economical interactions clearly shows that internal West African networks dealing with copper, salt, stones and staples predated the Trans-Saharian links with the Islamic world, leading to the conclusion that the so-called Arabic stimulus explanation can be dismissed. Finally, the articulation between the two towns of Djenne is addressed.
Keywords: Commerce transsaharien

The Ibāḍī Traders of Bilād al-Sūdān - van Riel, J.H. (The American University in Cairo, 2012)
Keywords: Commerce transsaharien

Sijilmasa, Zawila: Trans-Saharan Trade - Messier, Ronald A (World history, 2015)
Trans-Saharan trade dates back to antiquity. We know from numismatic evidence that from the end of the third century, an irregular gold coinage was issued at Carthage, and by the end of the fourth century there was a significant, if not regular, trans-Saharan
Keywords: Commerce transsaharien

العالقات القتصادية بين الدولة الرستمية وشعوب جنوب الصحراء (161-286هـ/777-909م) - لخضاري, زهية; لوناس, عائشة (جامعة الدكتور يحي فارس, 2015)
Keywords: Commerce transsaharien

Trading through Islam: the interconnections of Sijilmasa, Ghana and the Almoravid movement - Miller, James Andrew (The Journal of North African Studies, 2001)
Keywords: Commerce transsaharien

Saharan trade in the Roman period: short-, medium- and long-distance trade networks - Wilson, Andrew (Azania: Archaeological Research in Africa, 2012)
Keywords: Commerce transsaharien

Essouk-Tadmekka: an early Islamic trans-Saharan market town - Nixon, Sam (Brill, 2017)
Keywords: Commerce transsaharien

العلاقات التجارية بين الدولة الرستمية وبلاد السودان الغربي (006- 920هـ/770- 262م) - نوارخرخاش, أسماء (جامعة محمد خيضر, 2019)
Keywords: Commerce transsaharien

دور القوافل التجارية في التفاعل الثقافي بين ليبيا و المغرب العربي و ما وراء الصحراء و السودان في العصر الوسيط - القعود, زكية بالناصر منصور (آفاق الثقافة والتراث, 2014)
هدفت الدراسة إلى التعرف على دور القوافل التجارية في التفاعل الثقافي بين ليبيا والمغرب العربي وما وراء الصحراء والسودان في العصر الوسيط. وارتكزت الدراسة على عدة عناصر، تناول العنصر الأول ما المقصود بتجارة القوافل. وقدم العنصر الثاني نبذة تاريخية عن تجارة القوافل، العوامل التي دفعت العرب المسلمين إلى تجارة القوافل في ما وراء الصحراء، ومنها (طبيعة الدعوة الإسلامية، الأوضاع السياسية، العامل النقدي، واعتماد الاقتصاد الإسلامي على التجارة)، علاقة الدور الليبي الثقافي بالمغرب العربي وما وراء الصحراء. واستعرض العنصر الثالث حركة القوافل ومنها، القوافل التجارية ومن هذه الطرق (طريق نفوسة-زويلة، طريق فزان الممتد الى بلما وكانم بتشاد، طريق زويلة- سبها- ودان، طرابلس غدامس، طريق طرابلس إلى الجغبوب وسيوه والفرافرة والأقصر بصحراء مصر، طريق بنغازي إلى وادي ويمر على أوجله وجالو، وسرهن وكيانو وتاهينه)، وقوافل الحج. وركز العنصر الرابع على أهم محطات قوافل الحج ومنها محطة فزان، محطة غدامس. وأظهر العنصر الخامس التفاعل الثقافي بين ليبيا والمغرب على الصعيد المحلي في ليبيا، وكذلك على الصعيد الخارجي فيما وراء السودان.
Keywords: Commerce transsaharien

علاقات أباضيي ورقلة التجارية مع شمال الصحراء وجنوبها - شرف الدين, لمياء محمد سالم (مجلة العلوم الإنسانية, 2016)
هدفت الدراسة إلى التعرف على "علاقات أباضيي ورقلة التجارية مع شمال الصحراء وجنوبها". وأوضحت الدراسة أن موضوع خوارج بلاد المغرب الأباضيين قد حظي باهتمام ثلة من البحاث، إلا أن دراساتهم قد اتخذت وجهة سياسية أو مذهبية، ولم يحظ الخوارج الأباضية بدراسة لأوضاعهم الاقتصادية والاجتماعية بمعزل عن هاتين الوجهتين. وتناولت الدراسة نقطتين هما: النقطة الأولى "أوضاع التجمعات الأباضية حتى قيام الدولة الفاطمية "297ه/909م" حيث يعد البحث في أوضاع التجمعات الأباضية جزء على قدر من الأهمية في هذه الدراسة، ذلك أنه يحيل إلى معرفة التطورات في منطقة المغرب المتعلقة بالتجمعات الأباضية التي كان لدخول الفاطميين للمنطقة وقع عليها، إذ فر أغلب عناصرها إلى المناطق الجنوبية. وكشفت النقطة الثانية عن "علاقات أباضيي ورقلة التجارية مع شمال وجنوب الصحراء بعد قيام الدولة الفاطمية". ولعل من أبرز الدلائل على نشاط ورقلة التجاري، ما ورد في كتب الرحالة والجغرافيين من تعديد للطرق الرابطة بين الشمال والجنوب وبين الغرب والشرق مروراً بورقلة. واختتمت الدراسة بالتأكيد على أن توجه الأباضية إلى الجنوب/منطقة الواحات "ورقلة" والإستقرار به لم يكن إعتباطياً بقدر ما كان حلاً موضوعياً إرتآه الأباضيون، في مرحلة أولى فرار من القوات الفاطمية في أواخر القرن الثالث الهجري/التاسع ميلادين وفي مرحلة ثانية فراراً من الهلاليين الذين دخلوا بلاد المغرب في منتصف القرن الخامس الهجري/الحادي عشر ميلادي خاصة وأن هذه المناطق تمثل المواطن الأصلية لأغلب عناصرها.
Keywords: Commerce transsaharien

الصلات الاقتصادية والدبلوماسية بين المغرب الأوسط والسودان الغربي وأثرها على الحياة الثقافية بين القرنين الثاني والثالث الهجريين - مسعود, خالدي (دورية كان التاريخية, 2013)
يتناول المقال بداية الصلات بين المغرب الأوسط والسودان الغربي، حيث كانت العلاقات في مجملها تجارية في عهد الولاة وفي فترة حكم الرستميين، وعلى إثرها أقيمت علاقات سياسية تجلت مظاهرها في الوفود الدبلوماسية التي أرسلتها الدولة الرستمية لبلاد السودان منها بعثة محمد بن عرفة، وقد بينت الدراسة آثار الاتصال بين تجار الدولة الرستمية وأهالي السودان الغربي في الحياة الثقافية، فقد انتشر الإسلام ومعه المذهب الأباضي واللغة العربية والعادات والتقاليد الإسلامية كما تجلى الأثر الثقافي في المجال العمراني حسب ما توصل إليه عالم الآثار شاخت.
Keywords: Commerce transsaharien

The Conversion of Medieval Ghāna as Narrated by a Later Ibāḍī Scholar Abū al-ʿAbbās Aḥmad b. Saʿīd al-Darjīnī (d. ca. 670/1271, composed ca. 650/1252–53) - Yarbrough, Luke (Conversion to Islam in the Premodern Age: A Sourcebook, 2020)
The following semilegendary account of conversion in West Africa comes from the pen of Abū al-ʿAbbās al-Darjīnī, an Ibāḍī Muslim scholar, jurist, and poet from a Berber family in what is now west-central Tunisia. The Ibāḍīs are the major surviving representative of Kharijite Islam, the smallest of the religion’s three major early branches after Sunnism and Shiʿism. Today Ibāḍīs live mainly in Oman and Algeria. The book that contains this account, Kitāb Ṭabaqāt al-Mashāyikh, is al-Darjīnī’s principal work. It was written in response to a request from some Ibāḍī scholars of Oman for information concerning Ibāḍī history and learning in...
Keywords: Commerce transsaharien

Le commerce transsaharien médiéval vu par les sources ibadites - Prevost, Virginie (Journal asiatique, 2019)
Keywords: Commerce transsaharien

Trade and religion in the Central Sahara. The Ibāḍīs and Kawar - Vikør, Knut S. (From the Fjords to the Nile: Essays in honour of Richard Holton Pierce on his 80th birthday, 2018)
Keywords: Commerce transsaharien

Les réseaux transsahariens de la traite de l’or et des esclaves au haut Moyen Âge : VIIIe-XIe siècle - Botte, Roger (L'Année du Maghreb, 2011)
Keywords: Commerce transsaharien